Developing an Integrated Competency Framework for Madrasah Teachers: Bridging Scientific Literacy and Islamic Pedagogy - Elbina Mamla Saidah; Azam Ghazali; Mohd. Rafi Riyawi; Hamdi Pranata (Ta'dib, 2025)
Although the importance of madrasah teachers in bridging the gap between scientific and Islamic pedagogy is on the increase, the gap between the two fields still exists, as there is no well-organized framework of competences that can guide the teachers in their effective integration of the two domains in their classroom activities. This study aims to develop a competency framework for madrasah teachers that integrates scientific knowledge and Islamic pedagogy. Using the ADDIE model, the research was conducted up to the development stage, which included a needs analysis, conceptual design, and expert validation. Data were collected through interviews, observations, and documentation from madrasah teachers in Mandau Subdistrict, Bengkalis Regency, Riau Province. The resulting framework consists of four core components: Pedagogical Competence, Scientific Literacy, Integration of Islamic Pedagogy, and Professionalism & Spiritual Integrity. Expert validation involving five specialists in Islamic education, language, and visual design confirmed the framework’s relevance, clarity, and practicality, with validation scores ranging from “Fairly Appropriate” to “Highly Appropriate.” This study contributes to the growing discourse on integrated teacher development in Islamic education by offering a framework that balances spiritual values with contemporary educational demands. The framework is expected to serve as a reference for professional training programs in madrasahs and Islamic teacher education institution.